2005
DOI: 10.1021/jp0530451
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Hole Trapping in Photoexcited TiO2(110) Using a Surface Photoreaction

Abstract: The hole-induced photodesorption of chemisorbed O2 from a TiO2(110) single crystal has been employed to monitor the kinetics of electron-hole pair (e-h) formation and hole trapping. Excitation is produced by 3.4 +/- 0.05 eV photons at 110 K. Two separate O2 desorption processes have been found which are characteristic of low photon fluxes and high photon fluxes. At a critical photon flux, Fhnu(crit), the slow O2 photodesorption process suddenly converts to a fast process, signaling the saturation of hole traps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
250
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(268 citation statements)
references
References 61 publications
16
250
2
Order By: Relevance
“…From these results one may ascribe the strongly beneficial effect of WO 3 to the photocatalytic activity mainly to an enhanced hole-transfer kinetics to the electrolyte, while at the same time the detrimental effect of a too high WO 3 content may originate from charge trapping effects in the bulk. This is in line with literature, [36,39] which suggests the presence of WO 3 in TiO 2 to influence the re- combination rate of the photoproduced electron-hole (e À -h + ) pairs that may be either due to localized heterojunction formation [38] (due to mismatch of the TiO 2 and WO 3 band energies) or to the formation of activating surface species such as W VI states. The present work clearly favors the formation of specific surface features such as W VI states that act as mediators for charge transfer to the electrolyte.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…From these results one may ascribe the strongly beneficial effect of WO 3 to the photocatalytic activity mainly to an enhanced hole-transfer kinetics to the electrolyte, while at the same time the detrimental effect of a too high WO 3 content may originate from charge trapping effects in the bulk. This is in line with literature, [36,39] which suggests the presence of WO 3 in TiO 2 to influence the re- combination rate of the photoproduced electron-hole (e À -h + ) pairs that may be either due to localized heterojunction formation [38] (due to mismatch of the TiO 2 and WO 3 band energies) or to the formation of activating surface species such as W VI states. The present work clearly favors the formation of specific surface features such as W VI states that act as mediators for charge transfer to the electrolyte.…”
supporting
confidence: 91%
“…[23,24,27,28] Investigations of their photocatalytic properties have shown that these tubular layers can be more efficient than classical nanoparticulate layers of a comparable thickness. [29,[39][40][41] Self-ordered oxide nanotubes cannot only be grown on pure Ti, but also on other transition metals such as Mo, W, Ta, Nb, and so forth, and a full range of Ti alloys including TiW, TiNb, TiAl, TiMo, TiTa. [30][31][32][33][34] In the present work, we demonstrate a very strong effect of tungsten addition to the TiO 2 nanotubes in terms of their photocatalytic activity.…”
mentioning
confidence: 99%
“…They found that replacement of H in surface OH groups with D did not change the observed O − lineshape, but enrichment of the surface with 17 O did, leading them to conclude that holes did not trap at surface oxygen anion sites that were protonated. Additionally, some groups have also found evidence for subsurface hole traps [386,399,503,569,573]. Kerisit and coworkers [477] performed electrostatic calculations on hole (and electron) trapping at the unrelaxed R TiO 2 (110) surface.…”
Section: Hole Trappingmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] In addition to large surfaces, zeolites and other ordered mesoporous materials help control the size of the confined guest species during the process of deposition, therefore they become an obvious choice. Doping TiO 2 with metal ions for effective modification of the bandgap or separation of the photon-induced electronhole pair [20,21] is one of the most efficient methods reported for enhancement of catalytic activity. Transition-metalloaded silica-titania have also been studied extensively for their physicochemical properties and photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%